2018
DOI: 10.1021/acs.joc.8b00789
|View full text |Cite
|
Sign up to set email alerts
|

Tetrafluorobenzo-Fused BODIPY: A Platform for Regioselective Synthesis of BODIPY Dye Derivatives

Abstract: A novel route for the synthesis of unsymmetrical benzo-fused BODIPYs is reported using 4,5,6,7-tetrafluoroisoindole as a precursor. The reactivity of the 3,5-dibromo tetrafluorobenzo-fused BODIPY was investigated under nucleophilic substitution and Pd(0)-catalyzed cross-coupling reaction conditions. In addition to the 3,5-bromines, one α-fluoro group on the benzo-fused ring can also be functionalized, and an unusual homocoupling with formation of a bisBODIPY was observed. This new class of fluorinated BODIPYs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 71 publications
2
17
0
1
Order By: Relevance
“…Treatment of BOPHY 1 with 10 equivalents of bromine in chloroform [7a,19] led to the formation of 3,8‐dibrominated BOPHY 2 in 72 % yield, as shown in Scheme 1. BOPHY 2 was recrystallized from dichloromethane/methanol and directly used in reactivity studies, as shown in Schemes 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of BOPHY 1 with 10 equivalents of bromine in chloroform [7a,19] led to the formation of 3,8‐dibrominated BOPHY 2 in 72 % yield, as shown in Scheme 1. BOPHY 2 was recrystallized from dichloromethane/methanol and directly used in reactivity studies, as shown in Schemes 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
“…Although the reaction mechanism is still not fully understood right now, we propose a singlet electron transfer reaction between electron-deficient Ex-BODIPY 2b and electron-rich phenethylamine or 4-methylbenzenethiolate anion, which gave an anionic radical intermediate 2b . A previous report also found that aniline was used as a reducing agent to give the electron-deficient BODIPY dimer …”
Section: Resultsmentioning
confidence: 99%
“…A previous report also found that aniline was used as a reducing agent to give the electron-deficient BODIPY dimer. 11 X-ray crystallographic analysis of 7 and 6b allowed the unambiguous characterization of both unexpected products. Both 7 and 6b showed classical BODIPY structure features (Table S1), and the newly formed C−C single bonds at 3,5positions have the same lengths of 1.49 and 1.50 Å (Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among them, elegant research progress has been made on regioselective functionalization at the 3(5)-position of the BODIPY chromophore. While the 2,6-(β)­positions of the BODIPY core bear the least positive charge and are most susceptible to electrophilic attack, many β-functionalized BODIPYs have thus been synthesized from 1,3,5,7-tetramethyl-substituted BODIPY derivatives, where methyl groups block other possible reaction sites and enhance the overall electronegativities. For example, several 2-alkenyl- and 2,6-dialkenyl-1,3,5,7-tetramethyl-BODIPYs were prepared directly from a 1,3,5,7-tetramethyl-BODIPY via palladium-mediated C–H functionalization reactions by Burgess and co-workers .…”
Section: Introductionmentioning
confidence: 99%